Participation of eleventh-grade students of SMA Negeri 11 Yogyakarta in visual art learning - Nadhifa, Anggita Nur; Latifah, Arsianti (Universitas Negeri Yogyakarta, 2024)
This research aims to find out the participation of students and the factors that influence the active participation of class XI students at SMA N 11 Yogyakarta in learning art. This research uses a qualitative approach with phenomenological methods; data collection techniques used are observation, interviews with students and teachers, and documentation. The subjects of this research are teachers and students of class XI IPA. The results showed that (1.) Students' participation in learning art at SMA N 11 Yogyakarta includes direct and indirect involvement. 86% of students indicated that they were actively involved and enthusiastic about participating in learning; (2.) Overall, the indicators of learners' active participation in various aspects of art learning show a supportive learning environment and high motivation, both from learners and teachers; (3.) Factors that influence learners' active participation in art learning are learners' interest, concentration, attitude, cognitive knowledge, ability to complete tasks, and a conducive classroom atmosphere; (4.) Art education at SMA N 11 Yogyakarta has successfully achieved its goals by developing sensory sensitivity as learners can develop their creativity. Providing a stimulus for imaginative ideas has successfully stimulated the emergence of new imaginations in learners. Integrating art with other disciplines, such as learners' considering art, can increase creativity, and learners have a broad enough view so that they are able to appreciate art.